Pembelajaran Tari bagi Anak Usia Dini - Hilda Zahra Lubis; Nur Sa’adah; Alya Sabrina Ramdhani Hsb; Aulia Fitriani Muthe (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
Art cannot be separated from human life, including in the stages of childhood development. In addition to having aesthetic values, art also plays an important role in inspiring children's creativity and imagination. Early Childhood Education (PAUD), as a pioneer in the national education process, has a role in developing children's potential from various aspects, such as cognitive, language, art, morals, religion, movement, and socio-emotional. One important aspect in children's physical development is motor development, both gross and fine motor skills. One form of effective stimulus in developing children's motor skills is through learning dance. Dance provides space for children to practice body movement coordination, balance, and muscle strength, while stimulating self-expression. The basic elements in dance, such as movement, energy, space, and time, play an important role in supporting children's creativity in expressing themselves through body movements. Therefore, dance is one of the effective media in supporting children's motor development and creativity as a whole.